2002
DOI: 10.1007/s005200100282
|View full text |Cite
|
Sign up to set email alerts
|

Consultation audio-tapes: an information aid, and a quality assurance and research tool

Abstract: Facilities for audio-taping medical consultations are widely available, and an increasing proportion of cancer patients request and/or appreciate the offer of an audio-tape after an oncology consultation. We have examined the usefulness to patients and their families of audio-tapes of initial and follow-up consultations. We have used consultation audio-tapes as a research tool investigating doctor-patient communication. Audio-tapes may ultimately find a place as an audit tool to monitor oncologist performance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Exploring GP-patient consultations provides an essential portal to developing the quality of service delivery, patient satisfaction [see for example 29,49,121,122], and identifying outcomes of care [14,123]. A considerable effort has so far been invested in explaining various aspects of doctor-patient interactions [124].…”
Section: Discussionmentioning
confidence: 99%
“…Exploring GP-patient consultations provides an essential portal to developing the quality of service delivery, patient satisfaction [see for example 29,49,121,122], and identifying outcomes of care [14,123]. A considerable effort has so far been invested in explaining various aspects of doctor-patient interactions [124].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the tapes often reveal that much more information was shared than either party realized, suggesting that the tapes may even be protective. 136 …”
Section: Audiotapes As Communication Aidsmentioning
confidence: 99%
“…Despite evidence that these tools are effective for enhancing decision quality for preference sensitive conditions and are associated with appropriate, patient-centered care [3, 5, 12, 13], their adoption in the field of orthopaedic surgery has been limited [1, 14, 15], with a few notable exceptions. A group of investigators from the Group Health Cooperative reported high satisfaction among all stakeholders and reduced utilization of surgery and overall costs after implementation of decision aids for patients with hip and knee arthritis [16, 17].…”
Section: Introductionmentioning
confidence: 99%